Additive manufacturing of austenitic alloys with high strength and high ductility by selective laser melting - Sun, Zhongji (Nanyang Technological University, 2020)
Selective laser melting (SLM) is a popular powder bed fusion technique used for manufacturing of metal parts. Due to its high-energy laser heat source, SLM process creates a high thermal gradient and fast cooling rate. As a result, it tends to generate a fine microstructure with high dislocation densities and small grain size. Since it’s a layer-by-layer manufacturing process, there is a potential for microstructural control within a single build. This study thus aims to understand the mechanisms of microstructural control for SLM process. Specifically, it aims to achieve a desirable microstructure with improved the mechanical properties. Two types of alloys with austenitic crystallographic structures were fabricated in the current work, namely stainless steel 316L (SS316L) and high-entropy alloy AlxCoCrFeNi. It is found that with proper parameter optimization, the microstructure of SS316L could be successfully manipulated to enhance both strength and ductility concurrently as compared to the base material. As for AlxCoCrFeNi, hot cracking was found to occur in CoCrFeNi, proper composition adjustment is shown to successfully minimize the hot crack density and improve its mechanical performance.